The effectiveness of the goat value chain on poverty reduction among smallholder farming households in Shurugwi District’s Ward 9 - Phiri, Edwin (Midlands State University, 2017)
Goat production has been argued to offer an alternative and potentially lucrative livelihood option to poor subsistent farmers in Southern Africa. Many small-scale farming families raise indigenous goats which are considered to be the poor-man’s cattle due to their relative importance to the asset base of poor farming households. The practical implementation of poverty alleviation and reduction interventions at community level however often falls short of expectations and this study sought to complement and add to the emerging critique of these interventions, with a particular focus on the impact that the Goat Value Chain has had on poverty reduction. The study was informed by the Sustainable Livelihoods Approach and was delimited to Ward 9 of Shurugwi district where it explored the degree to which the Goat Value Chain has been effective in reducing poverty in view of the fact that it has been promoted as a means to support income generation among the rural, poor smallholder farming households.